Pertumbuhan Laba Perusahaan Pada Perusahaan Sektor Property & Real Estate - Keri Boru Hotang; Alvian Mahdi (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2023)
Purpose: This research aims to determine the effect of Net Profit Margin and Debt to Equity Ratio on Profit Growth. Design/methodology/approach: This research uses quantitative data, the sample in this research is 15 companies in the property & real estate sector listed on the Indonesia Stock Exchange in the period 2018 – 2022. The analysis technique used to test the hypothesis is multiple regression analysis using Eviews 9 software. Findings: The results of this research show that the Net Profit Margin variable has a positive and significant influence on Profit Growth. The Debt to Equity Ratio variable has a negativeand significant influence on Profit Growth. Research limitations/implications: This research discusses Profit Growth and other factors such as Net Profit Margin and Debt to Equity Ratio which focuses on property & real estate sector companies. Keywords: NPM, DER, Profit Growth Paper type - Research paper